Ophioglossaceae : an exomorphological approach with emphasis in South American species - Meza Torres, Esteban Ismael (2013)
An update about exomorphology of Ophioglossaceae family, with special reference to South American species is provided. The morphological characters that have been described in the literature by classical authors are discussed from the perspective of new observations, and its main morphological features are given. In this contribution it recognizes in South American the following genera: Botrychium Sw., Botrypus Micx., Sceptridium Lyon. Ophioderma Nakai (included Cheiroglossa C. Presl.), and Ophioglossum L. It proposed the term "angiostroma" to describe fertile portion of sporophore.